Child Labor and Resistance to Change - Giorgio Bellettini; Carlotta Berti Ceroni; Gianmarco I.P. Ottaviano (Fondazione Eni Enrico Mattei (FEEM), 2003)
We study the interactions between technological innovation, investment in human capital and child labor. In our setting new technologies require new skills and new skills can be developed only through schooling. In a two-stage game, first firms decide on innovation, then households decide on education. In equilibrium the presence of inefficient child labor depends on parameters related to technology, parents' altruism and the diffusion of firm property. When child labor exists, it is due to either firms reluctance to innovate or households' unwillingness to educate or both. The optimal policy to eliminate child labor depends crucially on its underlying cause. We show that, in some cases, compulsory schooling laws or a ban on child labor are welfare reducing, while a subsidy to innovation is the right tool to eliminate child labor and increase welfare.
Keywords: J24; O31; 330; Child labor; Innovation; Kinderarbeit; Technischer Fortschritt; Bildungsinvestition; Theorie